2016
DOI: 10.5980/jpnjurol.107.155
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of the Enzalutamide Treatment for Castration-Resistant Prostate Cancer

Abstract: (Objective) Enzalutamide is an oral androgen-receptor inhibitor that prolongs survival in men with castration-resistant prostate cancer (CRPC). We retrospectively evaluated clinical efficacy and safety of enzalutamide in CRPC. (Patients and methods) We reviewed clinical records of 73 patients who had received enzalutamide for the CRPC at Showa University and affiliated 7 hospitals. Enzalutamide was given at a dose of 160 mg/day, but some patients were treated at lower dose because of there age or poor performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…Notably, elevated PSA expression in 2D co-cultures of 22Rv1 with wild type fibroblasts treated with enzalutamide corresponded with elevated proliferation in 3D co-cultures of 22Rv1 and wild type fibroblasts treated with enzalutamide. A similar phenomenon has been seen in patients, where PSA flares result from enzalutamide treatment [46]. As demonstrated in our 3D cocultures, inhibition of both stromal and epithelial CD105 was necessary to suppress the proliferative effects of ADT on prostate cancer epithelia.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, elevated PSA expression in 2D co-cultures of 22Rv1 with wild type fibroblasts treated with enzalutamide corresponded with elevated proliferation in 3D co-cultures of 22Rv1 and wild type fibroblasts treated with enzalutamide. A similar phenomenon has been seen in patients, where PSA flares result from enzalutamide treatment [46]. As demonstrated in our 3D cocultures, inhibition of both stromal and epithelial CD105 was necessary to suppress the proliferative effects of ADT on prostate cancer epithelia.…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that ENZ is a welltolerated treatment option for CRPC in Japanese patients although physicians select its reduced doses. Although 71.4% of the patients in this study were administered reduced doses of ENZ due to their age and past medical history (e.g., cerebral infarction and polypharmacy), the efficacy of ENZ as represented by PSA response rates was found to be better than that reported in previous studies, where the standard dose of ENZ (i.e., 160 mg/day) was commonly used (2,3,6,7,10,11,16,25,(27)(28)(29)(30)(31)(32). One possible reason for the efficacy of reduced ENZ doses is that C SS, ENZ might suffice to treat CRPC.…”
Section: Discussioncontrasting
confidence: 62%
“…Another possible reason for the efficacy of reduced ENZ doses is the low level of baseline PSA in our cohort. A previous study reported the baseline PSA level as one of the crucial factors in determining the effects of ENZ therapy on Japanese patients (11). That is, the median baseline PSA level in CRPC patients with a PSA decline of >50% was 23.4 ng/ml, which was relatively lower than that in cases with a PSA decrease of <50% (median, 41.5 ng/ml) (11).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations